2002
DOI: 10.1111/j.1095-8649.2002.tb02388.x
|View full text |Cite
|
Sign up to set email alerts
|

Static habitat partitioning and dynamic selection by sympatric young Atlantic salmon and brown trout in south‐west England streams

Abstract: Direct underwater observation of micro-habitat use by 1838 young Atlantic salmon Salmo salar [mean L T 7·9 3·1(..) cm, range 3-19] and 1227 brown trout Salmo trutta (L T 10·9 5·0 cm, range 3-56) showed both species were selective in habitat use, with differences between species and fish size. Atlantic salmon and brown trout selected relatively narrow ranges for the two micro-habitat variables snout water velocity and height above bottom, but with differences between size-classes. The smaller fishes <7 cm hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 40 publications
2
27
0
1
Order By: Relevance
“…Intraspecific size-class competition and size-dependent predation risk may also affect the diets of trout. Whatever the reason, the fact remains that large fish forage more in pools (Bremset & Berg 1997;Heggenes et al 1999Heggenes et al , 2002, where surface feeding is presumably favoured, whereas small fish forage in riffles (Heggenes 1996;Mäki-Petäys et al 1997), where benthic foraging should be favoured (Nakano 1994;Dineen et al 2007a). Even predation risk has been invoked to explain this differential habitat use by large and small fish (Power 1987;Schlosser 1987;Lima & Dill 1990;Greenberg 1994;Greenberg et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Intraspecific size-class competition and size-dependent predation risk may also affect the diets of trout. Whatever the reason, the fact remains that large fish forage more in pools (Bremset & Berg 1997;Heggenes et al 1999Heggenes et al , 2002, where surface feeding is presumably favoured, whereas small fish forage in riffles (Heggenes 1996;Mäki-Petäys et al 1997), where benthic foraging should be favoured (Nakano 1994;Dineen et al 2007a). Even predation risk has been invoked to explain this differential habitat use by large and small fish (Power 1987;Schlosser 1987;Lima & Dill 1990;Greenberg 1994;Greenberg et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The parameters used in the viewshed analysis were an observer (i.e. fish) height of 0.05 m (see Heggenes et al, 2002), a field of view of 2008 and a visual range of 1.5 m. A field of view of 2008 was chosen to reflect where most aggressive attempts are directed (Keeley and Grant, 1995). The visual range of 1.5 m represents the maximum chase radius of age 2þ Atlantic salmon in Catamaran Brook (Keeley and Grant, 1995).…”
Section: Data Collectionmentioning
confidence: 99%
“…Current velocity data (AE0.01 m s À1 ) were recorded for each salmon, as well as averaged for each quadrat, using a one-dimensional Marsh-McBirney flow meter , oriented into the current. Current velocity for each individual Atlantic salmon (hereafter referred to as fish velocity) was recorded following each survey at each flagged position, at 0.05 m above the substrate to estimate snout velocity (Heggenes et al, 2002) and at 40% of the water column depth to estimate mean velocity (Hynes, 1970). Both snout and mean velocity for each fish were averaged per quadrat for each of 2002 and 2003 (n ¼ 8).…”
Section: Data Collectionmentioning
confidence: 99%
“…This is because numerous field studies have shown that there is a positive correlation between body size and the relative contribution of surface-drifting prey to the diet of salmonids, [40][42], [61]. Moreover, large, dominant salmonids inhabit pools [62][64] and forage in the water column, where they encounter and use generally large and conspicuous surface-drifting terrestrial invertebrates [19], [22], [43]. In contrast small fish spend most of their time in riffles [61], [65]–[67], where they forage mainly on benthic prey [42], [68].…”
Section: Discussionmentioning
confidence: 99%